PROPOSIÇÃO E TESTE DE UM MODELO DE ESCOLHA DE CURSOS DE GRADUAÇÃO - Átila Simões da Cunha; Gustavo Quiroga Souki; Luiz Rodrigo Cunha Moura; Mário Teixeira Reis Neto (Revista Gestão Universitária na América Latina, 2015)
The expansion of undergraduate education in Brazil caused the growth of vacancies updemand, raising the need to better understand how students choose where to study. Theobjectives of this research are to identify the attributes considered for such a choice and theability of such attributes explain the belief of students have taken the right decision. To meetthese objectives it was done a survey based on a cross sectional sample of 1,823 students. Theresults showed thatthe "belief of having made the right decision" rests primarily on the"image of the institution" and "low". The "image of the institution" was explained by"teachers and quality of teaching", "status", "tradition and recognition", "professional andpersonal success", "accessibility of location", "infrastructure", "extracurricular activities" andthe "feasibility of implementing graduation." These and other attributes were identified andpresented in the hypothetical model proposed.